Sustainable utilization of humanure-based bio-product for Marigold (Tagetes erecta L) production in Tropical India - Kavya, P; Jothimani, P; Maheswari, M; Thavaprakaash, N; Kavitha, M; Sridevi, G; Patil, S G (Plant Science Today, 2025)
Ecological sanitation converts human waste into safe compost, known as humanure, offering a sustainable solution for managing faecal matter. This approach not only recycles nutrients but also reduces environmental pollution. Enriched humanure was prepared by mixing humanure, biochar and human urine in ratios of 1:1:1 and 1:1:1.5 and the mixture was enriched for 30 days. The pH, electrical conductivity (EC), nitrogen, phosphorous and potassium content of the bioinputs (humanure, biochar, human urine) alone and the enriched humanure (1:1:1 and 1:1:1.5) were characterized. To test the efficacy of the enriched humanure, field trials were conducted during the winter and summer seasons in Vridhachalam on marigolds (Hybrid-Bens tall) using a randomized block design with 11 treatments in three replications. Treatments included bioinputs alone, unenriched and enriched humanure, 50% enriched humanure + 50% recommended dose of fertilizer (RDF), RDF + farm yard manure (FYM) and FYM alone. Fertilizers and manures were applied based on the crop s' nitrogen requirement of 90: 90:75 kg/ha. The results showed significantly higher plant growth, flower yield (27.0 to 27.5 t/ha) and flower quality were recorded in the application of enriched humanure in the ratio of 1:1:1 followed by 1:1:1.5 compared to all other bio-inputs treatments and the control. Enriched humanure (1:1:1) proved the most effective treatment for improving marigold growth and yield.